IMS Version 8 implementation guide : a technical overview of the new features - Jäntti, Jouko (IBM redbooks., 2002)
In this IBM Redbooks publication, we describe the new features and functions in IMS Version 8. We document the tasks necessary to exploit the features, and identify migration, coexistence, and fallback considerations. We also identify specific hardware and software requirements that are needed to exploit certain enhancements. First we provide an overview, where we have grouped the various enhancements and their discussion into the categories availability and recoverability, performance and capacity, systems management, and application enablement. Then we have more detailed chapters for describing the individual enhancements. The base enhancements part of the book describes the base product enhancements that apply to all users migrating to IMS Version 8. The Parallel Sysplex enhancements part of the book describes enhancements in IMS Version 8 that apply to both existing users of IMS Version 6 or IMS Version 7 in a Parallel Sysplex environment and users that are considering sysplex functionality. The Common Service Layer part documents the Common Service Layer (CSL), new in IMS Version 8, which is the next step in IMS Parallel Sysplex evolution. The CSL enables IMS systems to operate in unison in an OS/390 Parallel Sysplex. The CSL components provide the infrastructure for an IMSplex. Please note that the additional material referenced in the text is not available from IBM.